2014
DOI: 10.2147/ott.s69776
|View full text |Cite
|
Sign up to set email alerts
|

Natural history of histologically moderate cervical dysplasia in adolescent and young women

Abstract: BackgroundAdolescent women are a special age group affected by human papilloma virus (HPV). Most guidelines recommend surgical treatment for high-grade cytological lesions. However, some reports have attempted to demonstrate that the immune system is fully capable of clearing the virus without using conization. Our aim in this study was to describe the outcome of women <25 years old with high-grade cytology pap smears and no histologically confirmed cervical intraepithelial neoplasm [CIN] III.MethodsThis prosp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 10 publications
(12 reference statements)
0
0
0
Order By: Relevance
“…( 5 ) There is a low incidence of cancer among adolescents and young women is low, and there is evidence that screening is less efficient for detecting lesions. ( 3 , 6 , 7 ) Sasieni et al ( 8 ) showed that screening in women aged 20–24 years did not affect cervical cancer incidence until the age of 30 years. This finding supports the recommendation of observation over treatment for young women (aged 13–25) with grade 2 cervical intraepithelial neoplasia (CIN), as 68% of these cases resolve on their own within 3 years.…”
Section: Introductionmentioning
confidence: 99%
“…( 5 ) There is a low incidence of cancer among adolescents and young women is low, and there is evidence that screening is less efficient for detecting lesions. ( 3 , 6 , 7 ) Sasieni et al ( 8 ) showed that screening in women aged 20–24 years did not affect cervical cancer incidence until the age of 30 years. This finding supports the recommendation of observation over treatment for young women (aged 13–25) with grade 2 cervical intraepithelial neoplasia (CIN), as 68% of these cases resolve on their own within 3 years.…”
Section: Introductionmentioning
confidence: 99%